(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
When we talk about the circus, why do we so quickly remember the figure of the bearded woman, while there are so few historical references to the presence of trans and gender-dissident artists in the circus scene? Here, trans performativities act as a tension to the onto-epistemological pillars of thought and the modern world. Based on reflections on aesthetics, politics and dissident epistemologies, this article analyzes the participation of trans and gender-dissident artists in the Brazilian circus, the discursive relationship between virtuoso and colonial imaginary, and then proposes the possible epistemic contours of a trans performativity in the circus.